Stabilitas Dimensi dan Setting Time Bahan Cetak Anatomis Kedokteran Gigi Dari Ekstrak Natrium Alginat Rumput Laut Merah (Kappaphycus alvarezii) Dari Desa Agel, Kecamatan Jangkar, Situbondo - Didin Erma Indahyani; Izzata Barid; Agus Sumono; Fitria Arifka Rahman (STOMATOGNATIC - Jurnal Kedokteran Gigi, 2023)
Alginate impression material is important in dentistry. In its clinical application, setting time is still considered too fast, and the alginate impression material must have dimensional stability in accordance with ANSI / ADA standard specification no.18. Alginate impression material has a main component, namely sodium alginate which is produced from the seaweed extraction process. In Indonesia, there are several types of seaweed, one of which is the Kappaphycus alvarezii (K. alvarezii). The seaweed from the village of Agel Situbondo has the potential to be a source of sodium alginate and has antibacterial and antioxidant effects. The aim of this study to analyze the dimensional stability and setting time of the alginate printing material with sodium alginate extract of kappaphycus alvarezii seaweed. The study was conducted using laboratory experimental methods with post-test only control group design, there were 2 groups, namely the commercial alginate printing material control group, and the alginate printing material treatment group with sodium alginate extract from the acid method, then the FTIR test was carried out. Then the two groups were tested for setting time and dimensional stability. The results of the FTIR test of red seaweed extract showed an absorption peak that was identical to that of sodium alginate. The results of the setting time test significantly took longer for the red seaweed alginate impression material than the control group, while the dimensional stability showed the same results. Conclusion: The results of the setting time test showed that the treatment group had a longer setting time than the control group and both groups had dimensional stability according to the standard. The results of the setting time test showed that the treatment group had a longer setting time than the control group and both groups already had dimensional stability in accordance with the standard.